2018
DOI: 10.1016/j.jeoa.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for old age in France: The roles of preferences and expectations

Abstract: This article assesses the roles of preferences and expectations on preparation for old age, employing unique data on French individuals aged 50+. The data do not only contain information on the general feeling to prepare for old age and on specific preparation activities in various domains, but also on risk and time attitudes, family and social altruism, and expected disability and longevity. Half of the sample reports preparing for old age. Future orientation emerges as an important predictor of preparation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…This may be due to the majority of the participants were males, educated, working before retirement and still work even after being retired, have more responsibilities and have more chances to exchanges experiences with their peers and friends and update their knowledge through different social media. These results in line with other studies done in Utah, Georgia, in New York State by Sörensen et al,(2017) (4) , in France by Apouey, (2018) (20) and in the U.S. state of Colorado by Yun et al, (2021) (2) , who reported the same finding. Contradictory to the present study a study done in Hong Kong by Bai et al, (2022) (18) , revealed that older persons showed lower levels of planning in all subdomains and appeared less likely to participate in care preparation activities.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the majority of the participants were males, educated, working before retirement and still work even after being retired, have more responsibilities and have more chances to exchanges experiences with their peers and friends and update their knowledge through different social media. These results in line with other studies done in Utah, Georgia, in New York State by Sörensen et al,(2017) (4) , in France by Apouey, (2018) (20) and in the U.S. state of Colorado by Yun et al, (2021) (2) , who reported the same finding. Contradictory to the present study a study done in Hong Kong by Bai et al, (2022) (18) , revealed that older persons showed lower levels of planning in all subdomains and appeared less likely to participate in care preparation activities.…”
Section: Discussionsupporting
confidence: 92%
“…13 In psychology and related fields, 'future orientation' is broadly defined as the extent to which an individual thinks about the future, anticipates future consequences, and plans ahead before acting. In a survey covering French respondents, Apouey (2018) explores this broader notion of time preferences over the future, and finds correlational evidence linking it to preparation for old age (showing, for example, in saving behaviour, home adaptation and ownership, but not in LTC insurance). Similarly to Reckers-Droog et al (2021), this preference parameter can therefore be seen as representing the marginal willingness to pay for health, but specifically oriented towards old age.…”
Section: Individualsmentioning
confidence: 99%
“…Individuallevel age-related changes affect how much older adults engage in behaviors that promote or protect health; these include increased need for assistance with activities of daily living, and diminished health status, as well as changes in information processing and social cognition. To initiate ARP in the health care arena, a level of awareness of the risks for disease-related disability is needed (Apouye, 2018;Slovic et al, 2004), but seriously considering one's chance of frailty or dependence is often unpleasant and thus avoided (Pinquart & Sörensen, 2002;Sörensen & Pinquart, 2000b). Indeed, older adults are more likely than the young to focus on affective information in the context of decisions (Finucane, 2008), especially positive (versus negative) information (Löckenhoff & L.L.…”
Section: Psychological Factors In Aging-related Preparationmentioning
confidence: 99%
“…A qualitative study by Denton et al (2004) shows that preparation for late life is associated with a forward‐looking future‐time perspective. Having a limited time perspective is linked to more preparation in one study (Fowler & Fisher, 2009), but, in others, expected longevity is related to more preparation for finances, housing, and health (Apouye, 2018; Kornadt & Rothermund, 2015) as well as general retirement preparation (Jacobs‐Lawson & Hershey, 2005). Participants who report clearer goal expectations for their future prepare more concretely for fitness, social relations, and leisure activities, whereas shorter subjective remaining lifetime is related to more preparation for housing, finances, emergencies, and health care four years later (Kornadt et al, 2018).…”
Section: Findings Regarding Arpmentioning
confidence: 99%